Odpowiedzi

2009-12-08T20:18:15+01:00
5p-2r=21\*5
3p+5r=-6/*2
25p-10r= 105
6p+10r=-12
31p=93//31
p=3
18+10r=-12
10r=30//10
r= 3
p=3
2009-12-08T20:25:54+01:00
5p-2r=21/*5 4x+5y=12,3/×(-3)
3p+5r=-6/*2 3x-2y=-4/×4
25p-10r=105 -12x-15y=-36,9
6p+10p=-12 12x-8y=-16
31p=93/÷31 -23y=-52,9
p=3 y=2,3
5×3-2r=21 4x+5×2,3=12,3

p=3 y=2,3
15-2r=21 4x+11,5=12,3

p=3 y=2,3
-2r=6 4x=0,8

p=3 y=2,3
r=-3 x=0,2

2x+3y=0,5
3x+y=-1/×(-3)

2x+3y=0,5
-9x-3y=3
-7x=3,5
x=-0,5

2*(-0,5)+3y=0,5
x=-0,5

-1+3y=0,5
x=-0,5

3y=1,5
x=-0,5

y=0,5
x=-0,5